Sustainable Urban Planning Challenges in the Peri-Urban Landscape: Evaluating LULC Dynamics and the Policy Effectiveness of the Chattogram Metropolitan Region, Bangladesh - Md Mustiafiz Al Mamun; Steffen Nijhuis; Caroline Newton (Land, 2024)
Understanding the dynamics of land use and land cover (LULC) change in today’s context of rapid urbanization is critical for sustainable urban planning and environmental conservation. Therefore, the research aim is to understand the LULC changes in the Chattogram Metropolitan Area and to assess the policy implications of these changes for sustainable urban development. Through a comparative analysis of LULC maps for two periods (1997–2007; 2007–2017), we investigated the transformation of a detailed planning zone before and after Detailed Area Plan (DAP) approval. Using quantitative data analysis and policy review, we elucidated the impacts of urbanization trends on local ecosystems—specifically the conversion of forest cover and waterscape use. The findings reveal a significant conversion of forested and waterscape areas to urban and peri-urban landscapes, highlighting the urgent need for sustainable planning interventions that focus on these peri-urban areas. The study further critiques the DAP’s effectiveness, revealing a disconnect between regional policy implementation and local outcomes. This research proposes a validated, scalable framework for urban master plans that adapts to the complex socioecological contexts of rapidly urbanizing regions.